Il rococò a Valencia e la sua applicazione nell'adorno architettonico. - GIANNOTTA, GAETANO (Scripta, 2019)
Rococo emerged in the city of Valencia in the central three decades of 18th century and it has been expressing itself in all forms of art. It reached the peak of its richness in interior decoration, first of all those of the palace de Dos Aguas and the nearby church of San Andrés. Its success ended because of arrival of Academism, with the establishment in 1768 of the Royal Academy of Fine Arts of San Carlos, which claims to control the arts under the sign of neoclassicism. The Rococo has been always relegated to the last pages of the evolution of the Valencian Baroque. Nowadays, an independent study of the Valencian Rococo and its stylistic sources, of the models it employs, of its relations with previous styles, of the reasons of its thirty-year success, is still missing. This article pretends to shed light on these aspects, trusting that further studies can enhance the products of one of the richest periods in the history of Valencian art.